Mediação cultural no SIBIUFS: propostas de ações integradoras de atividades culturais - Sales, Aline Rodrigues de Souza (2020)
In the development of cultural mediation, the University Libraries emerge as a space of knowledge, exchange of information and construction of meaning. This work aims to investigate the role of the University Library as a cultural space, analyzing how it can become a space of cultural mediation, through the development of artistic and cultural policies that promote access to culture in the community in which it is inserted. Its main theme is cultural mediation, in the context of Information Science, and its general objective is to analyse the cultural mediation process and cultural practices within the SIBIUFS. As specific objectives it proposes to: explore the concept of cultural mediation in University Libraries; relate the notion of culture and community in the construction of the mediation process; identify the perception of SIBIUFS librarians regarding cultural mediation and propose a plan of action for cultural mediation in the SIBIUFS. It is an exploratory and descriptive research, of qualitative approach, which used bibliographic and documentary research, bringing reflections involving authors such as Quintela (2011), Perrotti and Pieruccini (2007), Cavalcante and Rasteli (2014) who highlight cultural mediation as an instrument for learning and dissemination of culture. For data collection a questionnaire was applied to the librarians of SIBIUFS. It was found that most SIBIUFS librarians understand the importance of the cultural mediation process in the University Library, and that cultural mediation happens eventually, but that it can be expanded.